Plant Metaphors in Indonesian Proverbs - Fauzi, Muhammad Ivan; Nirmala, Deli (Lingua Cultura, 2020)
This research was related to the use of plant metaphors in Indonesian proverbs. It was aimed to describe (1) the use of the name of the plants in Indonesian proverbs; (2) plant metaphorical interpretation in Indonesian proverbs. The data used were written data from the Indonesian proverbs dictionary by Badudu and the collection of proverbs by Lestari. The proverbs in the proverb book collections were observed, collected, and selected based on the topic using the plant names in Indonesian proverbs. The result shows that there are plant names used in the proverbs. Those are (1) the parts of the plant consisting of seeds, roots, stems, branches, leaves, and flowers; (2) plant classification based on the seed is dicot and monocot. Dicot plant includes pomegranate, nuts, coffee, jackfruit, yam, chili, ‘cempedak’, durian, limes, and pepper. In contrast, monocot plants are bamboo, cucumber, rice, grass, sugar cane, roses, bananas, corn, coconut, turmeric, and betel. The interpretation of the metaphorical meanings shows that proverbs tell the plants as a representation of strength and weakness, good attitude, fortune, the simple life, and the bad things.